The Diaspora Project on Education Sector: Cultivating Positive Perception of Indonesia Through International Education - Indraswari, Ratih; Aryani, Nyoman Mas (Udayana Journal of Law and Culture; Vol 3 No 2 (2019): The Dynamics of Global SocietyDO - 10.24843/UJLC.2019.v03.i02.p01, 2019)
The massive support to develop a new category of Indonesian Diaspora that is called as a “special friends of Indonesia’ (Indonesianist) seems would remain become a domain of academic and public debates. The existing Indonesian law and regulations, even though have been amended many times and during the debates on law creating process have tried to adopt the model of dual citizenship, do not affirm this new category. Despite this current legal situation, this article argues that this special friend can be cultivated from the international education section . This paper is academic research in the field of social sciences, especially international relations that analyzes statements, views, and opinion by government officers,  diaspora, and Indonesianists as well as some law and regulations. The research suggests that the concept of Special F riend s of Indonesia (Indonesianists) is too broad and poses a challenge for the conceptual and legal definition . Fully considering the high contribution of Indonesianist, nurturing of future Indonesianist - especially through student mobility programs - is best to take place in the situation allowing for exposure and socialization process to be built internally .